Use of fluorescence imaging and spectrometry in detection of oral squamous cell carcinoma and oral potentially malignant disorders - Vivek Nayyar; Pramila Thapa; Dalip Singh Mehta; Rahul Yadav; Krushna Bhatt; Varun Surya; Deepika Mishra (Oral Oncology Reports)
Objective: Changes in the autofluorescence of cancerous tissue in comparison to normal tissue due to alteration in the endogenous fluorophores and protein like NAD and FAD has been utilized in various oral cancer screening devices. But potential of fluorescence imaging and spectrometry with exogenous flourorophore has yet to be explored for real time oral cancer detection. Material and methods: In this study, 80 clinically suspicious cases of oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMDs) were screened with fluorescence imaging and spectrometry device before biopsy. On fluorescence imaging under blue light (480 nm) after application of fluorescein dye application, high fluorescence intensity from the site of lesion in comparison to contralateral normal mucosa was seen. Results: Fluorescence spectra of cancerous tissues and normal tissues show that there was a 4.36 nm of red shift in cancerous tissue. While OPMD tissues showed red shift of 3.42 nm. However, no difference in terms of red shift was found between the OPMD with dysplasia and OPMD without dysplasia. Conclusion: Fluorescence intensity was not helpful in differentiating OPMDs and OSCC cases. Further research is required to explore this optical technique for early detection of precancerous and cancerous lesions.